2016
DOI: 10.1016/j.jhydrol.2016.04.042
|View full text |Cite
|
Sign up to set email alerts
|

Evapotranspiration partitioning, stomatal conductance, and components of the water balance: A special case of a desert ecosystem in China

Abstract: Partitioning evapotranspiration (ET) into its components reveals details of the processes that underlie ecosystem hydrologic budgets and their feedback to the water cycle. We measured rates of actual evapotranspiration (ET a), canopy transpiration (T c), soil evaporation (E g), canopy-intercepted precipitation (E I), and patterns of stomatal conductance of the desert shrub Calligonum mongolicum in northern China to determine the water balance of this ecosystem. The ET a was 251±8 mm during the growing period, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(24 citation statements)
references
References 80 publications
2
22
0
Order By: Relevance
“…Wei et al (2017) stated that most isotope-based studies report higher transpiration fraction than nonisotopebased measurements. Zhao et al (2016) used sap flow measurements in the middle reaches of the HRB and found that T/ET of the Calligonum shrub ecosystem was about 0.66 during the growing season (May-September) from 2008 to 2010, which is similar to the result obtained here (0.67 ± 0.06) for the T. ramosissima shrub ecosystem. Comparisons indicate that T/ET varied among the different ecosystems in the HRB and the modeling results are comparable with the available results within the HRB using other observation methods.…”
Section: 1029/2018jd029680supporting
confidence: 83%
See 1 more Smart Citation
“…Wei et al (2017) stated that most isotope-based studies report higher transpiration fraction than nonisotopebased measurements. Zhao et al (2016) used sap flow measurements in the middle reaches of the HRB and found that T/ET of the Calligonum shrub ecosystem was about 0.66 during the growing season (May-September) from 2008 to 2010, which is similar to the result obtained here (0.67 ± 0.06) for the T. ramosissima shrub ecosystem. Comparisons indicate that T/ET varied among the different ecosystems in the HRB and the modeling results are comparable with the available results within the HRB using other observation methods.…”
Section: 1029/2018jd029680supporting
confidence: 83%
“…Transpiration represents the largest loss of water from ecosystems (Berkelhammer et al, 2016;Sun et al, 2014), and the quantification of T/ET still faces many uncertainties. Understanding the seasonality of T/ET can reveal details of the processes that underlie ecosystem hydrological budgets and their feedback to the water cycle (Kool et al, 2014;Li et al, 2013;Velpuri & Senay, 2017;Wen et al, 2016;Zhao et al, 2016). The T/ET can vary between 20% and 95% across ecosystems (Berkelhammer et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…This study used ecophysiological indicators to assess drought responses of a broad range of plant species native to semi-arid Western Australia in order to inform seedling performance in drought prone environments (Donovan & Ehleringer, 1991;Zhao et al, 2016). Plant stomatal conductance and the level of leaf conductance are strongly associated with soil water potential; thus, the selection of these plant measurements as indicators for seedling responses to drought enabled us to identify variation in species responses throughout the entire drought period and the threshold at which seedlings desiccated (Franks, 2004;Tyree & Zimmermann, 2013).…”
Section: Plant Morphology and Ecophysiological Characteristics Are Inmentioning
confidence: 99%
“…The average annual temperature and precipitation over the past five decades are around 5.4 °C and 204.0 mm, respectively, with the annual potential evaporation of 2365.0 mm [45]. Spring wheat and maize (C4 plant) are the major crops in this site, of which spring wheat is generally sown in late March and harvested in the middle 10 days of July, while maize is sown in late April and harvested in the middle 10 days of September [46]. The maximum canopy height and the maximum LAI are 2.1 m and about 5.6 m 2 m −2 , respectively.…”
Section: Introductionmentioning
confidence: 97%
“…This site represents an extremely arid region with scarce precipitation (116.8 mm per year) and high potential evapotranspiration. The potential evaporation is approximately 3755.0 mm per year and the average temperature is about 9.6 • C per year, with a frost-free period of 165 days [46]. Vegetation covers ranging from 15% to 20% and consists of desert shrubs comprising Populuseuphratica, Tamarix, and other arid region species.…”
Section: Introductionmentioning
confidence: 99%